Determination of Employee Job Satisfaction and Productivity of Port Loading and Unloading Workers: A Literature Review - Primadi Candra Susanto; Samuel Darwisman; Prima Widiyanto (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study is to develop hypotheses related to factors that affect the productivity of loading and unloading workers, especially in transportation sector companies. The approach used in this literature review study is descriptive qualitative. The data collection technique used was a literature study or review of relevant previous articles published between 2020 and 2025. The technique used in this literature review was comparative analysis. The data used in this descriptive qualitative approach comes from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of this literature review are: 1) Ability s influence the job satisfaction of loading and unloading workers; 2) Competence influences the job satisfaction of loading and unloading workers; 3) Leadership influences the job satisfaction of loading and unloading workers; 4) Ability influences the productivity of loading and unloading workers; 5) Competence affects the productivity of loading and unloading workers; 6) Leadership affects the productivity of loading and unloading workers; 7) Job satisfaction affects the productivity of loading and unloading workers; 8) Ability affects productivity through the job satisfaction of loading and unloading workers; 9) Competence affects productivity through the job satisfaction of loading and unloading workers; 10) Leadership affects productivity through the job satisfaction of loading and unloading workers.